Aurora kinase B-phosphorylated HP1α functions in chromosomal instability. Issue 12 (18th June 2019) - Williams, Monique M.; Mathison, Angela J.; Christensen, Trent; Greipp, Patricia T.; Knutson, Darlene L.; Klee, Eric W.; Zimmermann, Michael T.; Iovanna, Juan; Lomberk, Gwen A.; Urrutia, Raul A.
ABSTRACT: Heterochromatin Protein 1 α (HP1α) associates with members of the chromosome passenger complex (CPC) during mitosis, at centromeres where it is required for full Aurora Kinase B (AURKB) activity. Conversely, recent reports have identified AURKB as the major kinase responsible for phosphorylation of HP1α at Serine 92 (S92) during mitosis. Thus, the current study was designed to better understand the functional role of this posttranslationally modified form of HP1α. We find that S92-phosphorylated HP1α is generated in cells at early prophase, localizes to centromeres, and associates with regulators of chromosome stability, such as Inner Centromere Protein, INCENP. In mouse embryonic fibroblasts, HP1α knockout alone or reconstituted with a non-phosphorylatable (S92A) HP1α mutant results in mitotic chromosomal instability characterized by the formation of anaphase/telophase chromatin bridges and micronuclei. These effects are rescued by exogenous expression of wild type HP1α or a phosphomimetic (S92D) variant. Thus, the results from the current study extend our knowledge of the role of HP1α in chromosomal stability during mitosis.